Stock Versus CAD/CAM Customized Zirconia Implant Abutments – Clinical and Patient‐Based Outcomes in a Randomized Controlled Clinical Trial. (31st July 2016) - Schepke, Ulf; Meijer, Henny J.A.; Kerdijk, Wouter; Raghoebar, Gerry M.; Cune, Marco
Abstract: Background: Single‐tooth replacement often requires a prefabricated dental implant and a customized crown. The benefits of individualization of the abutment remain unclear. Purpose: This randomized controlled clinical trial aims to study potential benefits of individualization of zirconia implant abutments with respect to preservation of marginal bone level and several clinical and patient‐based outcome measures. Material and Methods: Fifty participants with a missing premolar were included and randomly assigned to standard (ZirDesign, DentsplySirona Implants, Mölndal, Sweden) or computer aided design/computer aided manufacturing (CAD/CAM) customized (Atlantis, DentsplySirona Implants, Mölndal, Sweden) zirconia abutment therapy. Peri‐implant bone level (primary outcome), Plaque‐index, calculus formation, bleeding on probing, gingiva index, probing pocket depth, recession, appearance of soft tissues and patients' contentment were assessed shortly after placement and one year later. Results: No implants were lost and no complications related to the abutments were observed. Statistically significant differences between stock and CAD/CAM customized zirconia abutments could not be demonstrated for any of the operationalized variables. Conclusion: The use of a CAD/CAM customized zirconia abutment in single tooth replacement of a premolar is not associated with an improvement in clinical performance or patients' contentment when compared to the use of a stock zirconia abutment.